2022
DOI: 10.3389/fimmu.2022.922111
|View full text |Cite
|
Sign up to set email alerts
|

Two Main Cellular Components in Rheumatoid Arthritis: Communication Between T Cells and Fibroblast-Like Synoviocytes in the Joint Synovium

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that endangers the health of approximately 1% of the global population. Current RA medications on the market mainly include non-steroidal anti-inflammatory drugs, biological agents, and disease-modifying drugs. These drugs aim to inhibit the overactivated immune response or inflammation of RA, but they cannot cure RA. A better understanding of the pathogenesis of RA will provide a new understanding to search for RA targets and for drug development. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…22 Macrophages and T cells interact closely with RA-FLSs in the joint synovium of patients with RA. 4,23 MIR22-overexpressing RA-FLSs indirectly repressed M1 proinflammatory marker CD86 while inducing M2 antiinflammatory marker CD206 in THP-1 cell-derived macrophages (Figure 2L and M and Supplementary Figure 2E). In addition, the ratio of CD4 + T cell subtypes Th1/Th2 and Th17/Treg was also indirectly diminished by MIR22-overexpressing RA-FLSs (Figure 2O-R).…”
Section: Resultsmentioning
confidence: 96%
“…22 Macrophages and T cells interact closely with RA-FLSs in the joint synovium of patients with RA. 4,23 MIR22-overexpressing RA-FLSs indirectly repressed M1 proinflammatory marker CD86 while inducing M2 antiinflammatory marker CD206 in THP-1 cell-derived macrophages (Figure 2L and M and Supplementary Figure 2E). In addition, the ratio of CD4 + T cell subtypes Th1/Th2 and Th17/Treg was also indirectly diminished by MIR22-overexpressing RA-FLSs (Figure 2O-R).…”
Section: Resultsmentioning
confidence: 96%
“…For example, lung and oesophageal fibroblasts are responsive to LIGHT and IL-13, which can be secreted by CD4+ T cells in asthma or EoE (Antunes et al, 2018;Wen et al, 2019). On the other hand, the ability of fibroblasts to modulate T or B cell responses may be an important factor in RA, ILD and skin inflammation, amongst other diseases (Lai et al, 2021;Tu et al, 2022;Xu et al, 2022). In their cross-tissue fibroblast analysis, Korsunsky et al (2022) reported a cluster of inflammatory fibroblasts that are common to lung, intestine, joints and salivary glands and found that these cells express CXCL10 and CCL19.…”
Section: Leukocytesmentioning
confidence: 99%
“…RA-FLS exhibit a metabolic profile parallel to some tumors, thriving in a hypoxic environment with increased production of oxygen radicals and cytokines [ 12 , 13 , 14 ]. Under stressful conditions, FLS has the potential to initiate, coordinate, and perpetuate inflammatory processes through complex interactions with adaptive immune response cells [ 5 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%